Modelling the Effects of Currency Exchange Rate Volatility on Philippine Balance of Trade Using Granger Causality Test - Charlotte Sarsaba; Izon Garret Diano; Jamaica Daro; Catherine Gonzaga; Karyme Ishe Pasulojan; Mary Joy Teodosio; Joey Estorosos (Recoletos Multidisciplinary Research Journal, 2025)
Background: Trade contributes to a nation's economic development, and the exchange rate indicates a country's trade competitiveness. This study investigates the potential for a bidirectional causal relationship between exchange rate volatility and trade balance in the Philippines. Methods: The study uses the Granger Causality Test to determine and ascertain whether there is a two-way causative relationship between exchange rate volatility and the balance of trade in the Philippines using the time series analysis considering the period from 1990–2023. Results: The findings indicate that the balance of trade can influence and be a factor in the change and movement of exchange rate volatility due to factors such as the export-import of the country that reflects the demand and supply of currency, indicating that shifts in the trade balance can contribute to fluctuations in exchange rates. Exchange rate changes may be necessary to restore equilibrium in trade flows in response to shifts in the balance of trade, including improvements or deteriorations. Conclusion: The study, therefore, recommends utilizing trade-related tactics to improve the trade balance by enhancing exports while cutting down unproductive and unprocessed imports, attracting more foreign investments and more exportation for exchange rate stability.